Prior Exercise Reduces Fast-Start Duration and End-Spurt Magnitude during Cycling Time-Trial - Lima-Silva, A. E.; Correia-Oliveira, C. R.; Tenorio, L.; Melo, A. A.; Bertuzzi, R.; Bishop, D. (International Journal of Sports Medicine, 2013)
We examined the pacing strategy and the magnitude of the end spurt during a 200-kJ cycling time trial performed 12–14 h after an exercise protocol designed to reduce muscle glycogen content. 9 physically-active men performed 5 familiarization sessions and 2 experimental 200-kJ time trials in either a control condition (CON) or after an exercise protocol performed the previous evening that was designed to induce muscle glycogen depletion (EP). Mean total time was faster and power output was higher in the CON than in the EP (P<0.01). A fast-start was maintained until the 50-kJ section in CON, but only the 25-kJ section for EP (P<0.05). The power outputs during the 50-, 150- and 200-kJ sections, and the magnitude of the end-spurt, were significantly higher for the CON than for the EP condition (P<0.05). There was no significant difference in the rating of perceived exertion (overall feeling and feeling in legs) between conditions. In conclusion, a protocol designed to decrease muscle glycogen stores reduced the duration of the fast-start and the magnitude of the end spurt during a 200-kJ cycling time trial, impairing the overall performance.
Keywords: sports performance; pacing strategy; carbohydrate-restricted diet; glycogen; physical effort; perceived exertion